Factors affecting customer loyalty towards online games / Muhammad Fadhil Moktar - Moktar, Muhammad Fadhil (Faculty of Business and Management, 2018)
The significance attempt in this study is to examine the factors affecting customer loyalty towards online games. This study explores the relationship between five factors which consist of entertainment, sociality, challenge, control, and interactivity that could influence factor of customer loyalty towards online games. This study also tries to figure out what are the most factor that influencing factor of customer loyalty towards online games among students. Therefore, the entertainment gives the greatest impact on customer loyalty towards online game In order to perform the statistical analysis, Statistical Packages for the Social Science (SPSS) version 21.0 was used. By using the SPSS, the researcher could identify and test the reliability of the questions given, the descriptive statistics, and the relationship between each variable. The respondents for this study were 100 citizens of Melaka which focusing on students. Besides that, in this study, 100 sets of questionnaires had been distributed. All respondents will be responding from questionnaires given in order to get result on the factors affecting customer loyalty towards online games. This study was using descriptive research to collect the information that related in the factors affecting customer loyalty towards online games. Therefore, in this study, there are two ways in gathering data which included primary and secondary data.